Association of Serum Osteoprotegerin Levels with Bone Loss in Chronic Kidney Disease: Insights from the KNOW-CKD Study - Kim, Chang Seong (PLoS One, 2016)
Osteoprotegerin, a potent osteoclast activation inhibitor, decreases bone resorption and positively affects bone mineral density. This study examined the association between serum osteoprotegerin levels and bone loss in patients with chronic kidney disease, a condition associated with increased risk of mineral and bone disorders. The bone mineral densities of the lumbar spine, total hip, and femur neck were assessed by dual-energy X-ray absorptiometry; serum osteoprotegerin levels were measured at baseline for 1,423 patients enrolled in the prospective KoreaN cohort study for Outcome in patients With Chronic Kidney Disease (KNOW-CKD). Patients aged ≥50 years and with a T-score ≤ –2.5 were diagnosed as having osteoporosis. Multivariable linear regression analysis indicated independent association between serum osteoprotegerin levels and decreased bone mineral density in the lumbar spine (B: –0.489, 95% confidence interval [CI]: –0.883 to –0.095, P = 0.015), and total hip (B: –0.349, 95% CI: –0.672 to –0.027, P = 0.027). However, bone mineral density of the femur neck was not associated with serum osteoprotegerin levels in women. After adjustments, no independent association was found between serum osteoprotegerin levels and bone mineral density in men. In multivariable logistic regression analysis, serum osteoprotegerin levels were associated with increased risk of osteoporosis in women (odds ratio [OR]: 4.72, 95% CI: 1.35 to 16.52, P = 0.015), but not in men (OR: 0.21; 95% CI: 0.04 to 1.31, P = 0.095). To summarize, in female patients with chronic kidney disease, increased serum osteoprotegerin levels were independently associated with decreased bone mineral density in the lumbar spine and total hip, and with increased risk of osteoporosis. Therefore, the measurement of serum osteoprotegerin concentration might be useful as a surrogate marker for determining bone loss in patients with chronic kidney disease, especially for women, although not so much for men.